Digital Transformation, Innovation, and Competitive Advantage: Enhancing MSME Performance in Bitung, North Sulawesi - Sumakul, Grace Christien; Hibrida, Anas Romzy; Kolinug, Ferly Christian (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Micro, small, and medium enterprises (MSMEs) serve as vital components of the Indonesian economy, particularly in Bitung City, North Sulawesi. The dynamics of global competition, shifts in consumer behavior, and digital disruption necessitate that MSMEs embrace digital transformation and innovation. This study seeks to examine how digital transformation and innovation impact the performance of MSMEs, with competitive advantage acting as a mediating factor. Utilizing a quantitative approach, the research involved surveys conducted with 113 MSME operators in Bitung. Data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). Findings indicate that digital transformation significantly enhances both competitive advantage and performance. While innovation positively influences competitive advantage, it does not have a direct effect on performance. The study confirmed that competitive advantage mediates the relationship between digital transformation and innovation in relation to MSME performance. These results highlight that digital transformation serves as the foundation, with innovation acting as a catalyst, and competitive advantage being crucial for sustainably improving the performance of MSMEs